An Analytical Apparatus for Visual Imagery Applied in a Social-Behavioral Research. Issue 2 (August 2022) - Hannes, Karin; Siegesmund, Richard
Participant created visual data are increasingly being used in social-behavioral sciences projects. They have become a popular medium in community-based research adopting an arts-informed approach to study challenging life circumstances of community members. We argue that visual data can do more than just illustrate ideas or concepts, particularly in the process of research where participants contribute to the data collection phase. Visual images record the tacit meanings of the person who makes them, and they can—with the help of a researcher skilled in qualitative reasoning—form another stream of textual analysis. The authors developed an Analytical Apparatus for Visual Imagery (AAVI), constructed from the elements of art and the principles of design and other arts-based sources, and applied it to two different arts-based research projects where participants created visual images or artworks for analysis. Through a combination of storylines and the AAVI analysis, a deeper level of analytical interpretation and a better understanding of the complexity of human experience were reached, particularly in trying to understand the emotional layers linked to experiences.